PROMOSI PRODUK MELALUI MEDIA SOSIAL UNTUK MENINGKATKAN PEREKONOMIAN PADA PELAKU USAHA KERAJINAN AKRILIK - Karlinda, Ai Elis; Sari, Desi Permata; Arsyah, Rahmatul Husna (Transpublika Publisher, 2022)
The Covid-19 pandemic that has been plaguing Indonesia since 2020 has affected many people, particularly MSME. These MSME have an important role to play in boosting the local economy and improving the quality of life for everyone. Businesses can exist and compete thanks in part to their ability to compete and market their products effectively. Since the pandemic, many micro, small and medium-sized enterprises (MSMEs) have turned to e-commerce in an attempt to increase sales. However, the MSME actors' ability to use technology is still low. Changing the marketing model is a necessity for business actors who wish to have their products compete on the global market. Padang City Acrylic Craft business actors have a lot of issues when it comes to product marketing, and they still rely on traditional marketing and don't use social media effectively. The goal of this activity is to educate MSME owners about the advantages of social media marketing and teach them how to use social media to boost their product sales. Training and mentoring are the primary approaches. It is also possible to use social media to promote and market products as a result of these activities.